Genomics and Transcriptomics of 3ANX (NX-2) and NX (NX-3) Producing Isolates of Fusarium graminearum - Philip L. Walker; Sean Walkowiak; Srinivas Sura; E. RoTimi Ojo; Maria A. Henriquez (Toxins, 2025)
Fusarium head blight (FHB) is an important fungal disease caused by Fusarium graminearum and other Fusarium spp., resulting in significant yield losses across cereal grains. Recently identified F. graminearum isolates in Canada, capable of producing type A trichothecene mycotoxins 3ANX (NX-2, 7-α hydroxy,15-deacetylcalonectrin) and NX (NX-3, 7-α hydroxy, 3,15-dideacetylcalonectrin), demonstrated high levels of genetic diversity. While recent studies have detected this genetic and chemical diversity, little is known of the underlying molecular mechanisms and processes influenced by these distinct chemotypes and regional populations. In the current study, we used an -omics approach coupled with high-resolution mass spectrometry to characterize twenty F. graminearum isolates collected from five distinct regions across Manitoba. These data identified regional F. graminearum populations within Manitoba that demonstrate distinct genomic variation and patterns of gene expression, particularly within pathogenicity-associated processes. Further, we identified genetic variation and differential expression between isolates showing high and low levels of pathogenicity, allowing for the identification of previously characterized and novel putative pathogenicity factors. Lastly, we detected the production of 3ANX and/or NX mycotoxins within the majority of our twenty characterized F. graminearum isolates, suggesting the 3ANX chemotype may be more prevalent than previously expected in Canada. Ultimately, these findings highlight the diversity of F. graminearum across Manitoba and, more importantly, uncover specific genomic regions and candidate pathogenicity factors influenced by this diversity.